Breast cancer survivors' barriers and motives for participating in a group-based physical activity program offered in the community - Wurz, Amanda; St-Aubin, Anik; Brunet, Jennifer (Université d'Ottawa | University of Ottawa, 2015)
Purpose: The purpose of this qualitative study was to explore the barriers and motives experienced by women attending an 8-week group-based physical activity program offered in the community following treatment for breast cancer. Methods: Seven women were interviewed during the first and last week of the program. Data were analyzed using thematic analysis. Results: Factors that hindered women's continued participation could be subdivided into situational barriers, which encompassed community (i.e., distance of center and traffic) and institutional factors (i.e., competing roles and responsibilities), and internal barriers, which consisted of cancer-specific limitations. Motives for initial and continued participation were situational (i.e., gaining social support, networking, and being around similar others) and internal (i.e., feeling a sense of personal fulfillment, acquiring health benefits, and recovering from cancer). Conclusions: The findings contribute to a deeper understanding of women's motives to engage in a group-based physical activity program after treatment for breast cancer. Further, they underscore the necessity of considering situational and internal barriers when developing group-based physical activity programs to increase regular participation, optimize adherence, and reduce drop-out.
Keywords: Group-based physical activity; Breast cancer; Survivorship; Qualitative study; Community-based